(untitled) (Fiep Bulletin - online, 2011)
Dermatoglyphics, somatotype and strength of IFTO students in different maturational stages. This study was conducted with 192 students, officially registered in the Education, Science and Technology Federal Institute of Tocantins – IFTO, Campus of Araguatins-Brazil, in the age bracket from 14 to 17 years old. , sub-divided in masculine puberty groups (MPG n= 71) and masculine post-puberty (MPPG n= 41) and feminine puberty groups (FPG n= 28) and feminine post-puberty (FPPG n= 52). Identify the dermatoglyphic, somatotype and strength characteristics according to the maturational stages of the students compose one of the necessary stage for the sport orientation. Dermatoglyphic evaluation through the Dermatoglyphic Method of CUMMINS & MIDLO (1961) has been made; somatotypical evaluation through the HEATH-CARTER (1967) Technique has been made; sexual maturation test through the pubic hair auto-evaluation by the Method proposed by TANNER (1962) and MATSUDO (2005) has been made; Horizontal Jump and Vertical Jump determinate by the STANDING BROAD JUMP for explosive strength determination through the SARGENT JUMP TEST have been made. The dermatoglyphics results related with strength have shown P>0.05 and r of Pearson near to zero. Whereas the somatotype related with the dermatoglyphics and strength has shown 13 of 16 crossing with P>0.05. A significative difference hasn’t been found.